Efeitos térmicos na conversão ascendente de freqüências em Er3+ e propagação de pulsos em meios não lineares - Oliveira, Jonathas Matias de (2002)
In this work, we have investigated experimentally and theoretically the process of frequency upconversion at low temperatures in rare earth doped vitreous samples. A sample of chalcogenide glass doped with erbium ions (Er3+) was pumped with a laser source at 1.54 μm. We have observed, at room temperature, three different emission bands around 530 nm, 555 nm and 670 nm, originating from the excited state erbium levels 2H11/2, 4S3/2 and 4F9/2 to the 4I15/2 ground-state, respectively. A cryogenic system cooled the sample down to 4 K, and we have recorded many spectra in this range of temperature. We have observed relative increase in the intensity of the green fluorescence, which comes from the level 4S3/2, and also the vanishing emission of the 530 nm line around 210 K. For all emission lines, the frequency upconversion process has been accounted for with three photons absorbed from the pumping source, but saturation effects were observed above 10 mW of incident power. We have made a theoretical treatment of the experimental data and a numeric simulation, which has revealed that the observed behaviors are related to processes that involve step-wise photon absorption and phonon assisted nonradiative decay, both dependent on the temperature and phonon energy of the sample. We also present, in the third chapter, an analytic treatment of pulse propagation in nonlinear media. We have used a variational approach to predict the behavior of an optical pulse propagating in the vicinity of a two-photon resonance, where the third order nonlinearities may be enhanced and limits optical devices development. A possible solution for the problem is the propagation of a pulse with suitable profile and frequency chirp resulting in a balancing of the nonlinear effects.